A phase 2a randomized, double‐blind, placebo‐controlled, sequential dose‐escalation study to evaluate the efficacy and safety of ASP015K, a novel Janus kinase inhibitor, in patients with moderate‐to‐severe psoriasis. (19th June 2015) - Papp, K.; Pariser, D.; Catlin, M.; Wierz, G.; Ball, G.; Akinlade, B.; Zeiher, B.; Krueger, J.G.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Janus kinases (JAKs) mediate intracellular cytokine‐receptor signalling associated with plaque psoriasis. What does this study add? ASP015K is a novel JAK inhibitor with specificity for JAK3 and JAK1, which exhibits dose‐dependent reductions in psoriasis severity in patients with moderate‐to‐severe psoriasis, and was generally well tolerated in this phase 2a study.